Comparison of safety and efficacy of different endovascular treatments for symptomatic intracranial atherosclerotic stenosis: results from a single center - Lin, Qiao; Zhong, Kaiyi; Pan, Xiyue; Li, Congfang; Lu, Xiaozhen; Wang, Naidong (Frontiers in Neurology, 2025)
BackgroundSymptomatic intracranial atherosclerotic stenosis (sICAS) is one of the common causes of ischemic stroke. However, the treatment of sICAS has remained a challenge in the past with unfavorable findings. This study aimed to evaluate the effectiveness and safety of different endovascular treatment methods for sICAS.MethodsThe study involved 154 patients with sICAS who received endovascular treatment at Qingdao University Hospital between January 2021 and October 2023. Based on the characteristics of the lesions, three different types of treatments were performed: bare metal stent group (BMS group), drug-coated balloon group (DCB group), and drug-eluting stent group (DES group). The primary endpoints included the incidence of in-stent restenosis (ISR) in the 6-month, periprocedural complications, the rate of stroke recurrence in the area of the stented artery during the follow-up period, and modified Rankin score (mRS) at discharge, at 1-month, at 3-month, at 6-month of patients after stenting.ResultsThe incidence of perioperative complications did not differ significantly between groups (11.3% in the BMS group, 8.0% in the DCB group, and 6.1% in the DES group, p = 0.776). All patients (154/154) had successful reperfusion after endovascular treatment. The incidence of stroke during follow-up was 4.5% (7/154), with 5 (7.0%) patients in the BMS group, 1 (2.0%) patient in the DCB group, and 1 (3.0%) patient in the DES group. The restenosis rate in the BMS group [35.2% (25/71)] tended to be higher than that in the DCB group [6.0% (3/50)] and DES group [9.1% (3/33)]. In multivariate logistic regression analysis, endovascular treatment strategy and vessel distribution were significant independent risk factors for ISR within 6 months (p < 0.05).ConclusionAdverse events and success rates following stent implantation are comparable across therapy groups in individuals with sICAS. When compared to BMS, DES, and DCB reduce the risk of ISR, with the advantages of the DCB appearing to be greater for some high-risk patients with ICAS.